DESIGN AND FABRICATION OF A LABORATORY SCALE SHELL AND TUBE HEAT EXCHANGER - Hassan, Umar; Hassan, Tukur; Qozeem, Ibrahim Alapatira (FUDMA JOURNAL OF SCIENCES, 2025)
Heat exchangers are critical devices used across various industries to transfer thermal energy between fluids and one of the most important tools in heat transfer and thermodynamics courses. However, Nigerian public institutions often lack access to necessary and well-designed laboratory scale heat exchangers that are easily disassembled to provide students with practical, hands-on experience, limiting their understanding of the key engineering concepts. This paper presents the design, development and fabrication of a laboratory scale shell and tube counter-flow heat exchanger (STHE). Designing the laboratory scale model serves educational and experimental purposes, allowing students and researchers to analyze the thermal behavior, evaluate effectiveness and validate design equations. The design incorporates cost-effective and locally available materials, making it feasible for institution with limited resources. The system was design based on a counter-flow arrangement for maximum temperature gradient and higher heat transfer efficiency, while logarithmic mean temperature difference, LMTD was used to analyze the performance of the heat exchanger. The length for both shell and tubes of the model heat exchanger was 600mm with 8 numbers of tubes with mass flow rates of both hot and cold waters as 0.0194 kg/s and 0.0263 kg/s respectively. The test results showed that the heat transfer rate Q, LMTD and the overall heat transfer coefficient, U for the hot and cold sides of the shell and tube heat exchanger were (1630, 376.2) W, (53.1 for both) oC and (1615.6, 372.9) W/m2 oC respectively. The heat exchanger achieved an effectiveness of 35.97% which is far lower than...
Keywords: Shell and Tube; Counter flow; Heat exchanger; Heat transfer